Subspace Identification for Industrial Processes - Borjas, S. D. M.; Garcia, C. (Trends in Computational and Applied Mathematics, 2011)
Subspace identification has been a topic of research along the last years. Methods as MOESP and N4SID are well known and they use the LQ decomposition of certain matrices of input and output data. Based on these methods, it is introduced the MON4SID method, which uses the techniques MOESP and N4SID.